PENGARUH PENERAPAN SISTEM AKUNTANSI DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS INFORMASI AKUNTANSI - Ilham Dwi Ariyanto, (2017)
This research was conducted to test the application of accounting systems and the utilization of information technology to the quality of accounting information. The population in this research is the entire section on financial clerks Work Unit (SKPD) area of Devices in the area of Government of the city of Bogor. The number of samples that are used i.e. 50 respondents. The type of data in this research is quantitative data sourced from primary data. Method of data collection is done by way of disseminating a questionnaire. The scale used in drafting the questionnaire i.e. the ordinal scale. Analytical techniques used in this research using SPSS. The research results showed that the application of the accounting system significantly influential to the quality of the Accounting Information while information technology Utilization effect was not significant to the quality of accounting information.